Food Waste Valorisation for Biogas-Based Bioenergy Production in Circular Bioeconomy: Opportunities, Challenges, and Future Developments - Singh, Puneet Kumar; Mohanty, Pratikhya; Mishra, Snehasish; Adhya, Tapan Kumar (Frontiers in Energy Research, 2022)
Fossil fuel-based linear economy has inherent intricacies like environmental pollution and the continued need for energy sourcing. Consequently, there has been a shift to a more sustainable circular bio-economy, in which biomass waste is valorised for energy generation while reducing the bulk waste materials and greenhouse gas emissions. In modern bioeconomy, biogas is a primary energy production vehicle. Bio-based economy enabled technologies result in heat and electricity generation, considerable substitution of fossil fuels for transport, and also the manufacture of additional value-added products and byproducts of economic benefits. Wastes from industrial operations, agriculture and other anthropogenic activities like the food waste (FW) can be biodigested and transformed into valuable energy sources, nutrient-rich manure and specialty chemicals. However, for instance, although closed anaerobic membrane bioreactors can totally avoid microbial runoff, membrane fouling frequently affects the hydraulic performance. Recent developments in anaerobic digestion (AD) of FW have diversified into pretreatment, organic loading, additives supplementation, parametric optimisation and digestate recirculation to enhance the utility potential of biomass for energy and environment. These numerous anaerobic and microbial interventions support biomass valorisation and related processes, resulting in more efficient biomethanation. Valorisation of FW through biogas-based energy production could serve as an essential cog in the wheel of circular bioeconomy.